Production design rigid tube rib / Muhammad Amirul Zakaria - Zakaria, Muhammad Amirul (2022)
This Project are focuses on how to make all household who had faced problem such as flood to have at least one this boat. Unfortunately, this boat is too expensive for people because of its material. So, from that, the project is to replace the material for the sponson from Hypalon to the PVC pipe to lower the cost. Furthermore, the comparison the material for sponson were made by doing a Pugh method with both advantages and disadvantages. This paper also will talk about how the boat will be made with fiberglass material and the suitable method that will use to construct the boat. The end of this project will get a method to construct the boat using fiberglass and the detail drawing will be made for the next FYP.